2015
DOI: 10.1103/physrevb.92.104424
|View full text |Cite
|
Sign up to set email alerts
|

Spin wave eigenmodes in transversely magnetized thin film ferromagnetic wires

Abstract: We report experimental and theoretical studies of spin wave eigenmodes in transversely magnetized thin film Permalloy wires. Using broadband ferromagnetic resonance technique, we measure the spectrum of spin wave eigenmodes in individual wires as a function of magnetic field and wire width. Comparison of the experimental data to our analytical model and micromagnetic simulations shows that the intrinsic dipolar edge pinning of spin waves is negligible in transversely magnetized wires. Our data also quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Comparison of the simulated spectrum with that obtained by BLS shows a perfect agreement in the frequency of BM, while the experimentally obtained frequency of EM 2.5 GHz is higher than that observed in simulations. We emphasize that this result is in a good agreement with previous studies 10 , 32 . In particular, in ref.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Comparison of the simulated spectrum with that obtained by BLS shows a perfect agreement in the frequency of BM, while the experimentally obtained frequency of EM 2.5 GHz is higher than that observed in simulations. We emphasize that this result is in a good agreement with previous studies 10 , 32 . In particular, in ref.…”
Section: Resultssupporting
confidence: 94%
“…In particular, in ref. 32 , it was shown that, in magnetic nanowires, the experimentally observed frequencies of the edge modes are always higher than those obtained from micromagnetic simulations. This frequency mismatch was attributed to an extrinsic pinning of the magnetization at the edges of the nanowire due to the joint action of the edge roughness, edge dilution effects, the non-zero surface anisotropy, etc.…”
Section: Resultsmentioning
confidence: 86%
“…Such a high blue shift has been previously observed for auto-oscillatory edge spin-wave modes in AMR SHOs 15 . The edge spin-wave mode results from spatially inhomogeneous demagnetizing field at the nanowire edges that produces a magnetic potential well for spin-wave excitations 46,47 . The edge mode in nanowires exhibits maximum amplitude at the wire edge.…”
Section: Resultsmentioning
confidence: 99%
“…The field-frequency relation of the spin wave mode and thus the auto-oscillation frequency can be efficiently controlled via changing the nanowire width and thereby modifying its magnetic shape anisotropy 47 . For the nanowire magnetized by a transverse magnetic field, the resonance field increases (the resonance frequency decreases) with decreasing nanowire width 47 , as confirmed by our measurements of a 90 nm wide YIG/Pt nanowire described in the Supplementary Note 2 .…”
Section: Resultsmentioning
confidence: 99%